Effective ways of using Technology in Teaching - Mourya, Surinder Kumar; Singh, Tarandeep (Gyan Management Journal, 2022)
During last two decades, technology has evolved and is still evolv ing. Many people are becoming technologically adept and digital citizens.  Technology is essential to the creation and exchange of knowledge in the  teaching sector in the current digital era. When technology is used in the  classroom, it may improve teacher knowledge and aid in the learning and  motivation of the students. Social networking has been used to support  teaching over the past ten years, including its integration with online games  and educational content (Johnson & Germain-Froese, 2016). Technology  has also demonstrated its efficacy in the classroom, serving as a source of  inspiration and creating an environment conducive to real learning. But  there are still drawbacks to using technology in the classroom. Students  might misuse technology and easily become distracted. In addition, exces sive use of technology may impair students’ ability to think (Fetylyana  Nor Pazilah, 2019). This study looked at the best practices for integrating  technology into the classroom. It aims to identify the most efficient online  platforms and technological resources that teachers can use in their line of  work. For creating educational content, many of these tools are free and  simple to use. The purpose of this study is to determine how much aware ness there is among teachers and students at various colleges regarding the  use of technology in the classroom.
Keywords: Technology Teaching; Effective technological; Students easily; Diverted misuse; Technology frequent